Improved tribological properties of stainless steel by high temperature-alloyed tantalum gradient layer. (February 2022) - Bing, Zhou; Liu, Ying; Liu, Zhubo; Ma, Yong; Hei, Hongjun; Shi, Bang; Wu, Yanxia; Yu, Shengwang
Abstract: Tantalum (Ta) gradient transitional layer, which was prepared by double-glow plasma surface alloying technology, was designed to improve the tribological properties of AISI 304 stainless steel. The microstructure, morphology, mechanical and tribological properties of surface modified stainless steel were characterized and analyzed. The results showed that the modified Ta coating can improve the surface roughness and tribological properties of the AISI 304 stainless steel greatly. Furthermore, β-Ta is in the majority in gradient transitional layer and it show high critical scratch load. The thickness of Ta coating, surface roughness, load bearing capacity, friction coefficient and wear rate of Ta/AISI 304 increased first and then decreased. Especially, the sample with Ta alloyed time of 30 min show excellent tribological properties, which were closely related with high critical load, low surface roughness, and the phase transformation from metastable β-Ta to stable cubic α-Ta in less oxygen conditions at the role of frictional heat. Furthermore, there are α-Ta nanoparticles with assembled into nanoribbons on the counterface decreasing the friction and wear further. The present study provides useful guidance for the modification of AISI304 and a new prospect on the transition from β-Ta to α-Ta during the friction. Highlights: The surface roughness and wear rate of Ta modified AISI304 stainless steel decrease at least one order. β-Ta are in the majority in gradient transitional layer. The transformation from β-Ta phase to α-Ta phase during the friction. Low friction and wear mechanism of Ta layer.